2017
DOI: 10.11646/phytotaxa.291.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Two new combinations in Iberian Santolina (Compositae) based on morphology and molecular evidences

Abstract: The genus Santolina is represented in the Iberian Peninsula and Balearic Islands mainly by two complexes of species: S. rosmarinifolia aggr. and S. chamaecyparissus aggr., with a great similarity between the taxa included in each of these complexes. In the study of Santolina for the “Flora iberica” project, we prefer the species rank for the taxa with main differences in foliar and involucral bracts. Two new combinations, S. vedranensis and S. montiberica, are proposed here on the basis of our morphological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In the last two decades, López-Udias and co-workers (López-Udias & al., 1997;López-Udias & Fabregat, 2002) and especially Rivero-Guerra (2008a,b, 2011 and Rivero-Guerra & Laurin (2012) have studied the S. rosmarinifolia complex, so that its nomenclature and taxonomy seem to have become more stable than in the past. On the contrary, there is no taxonomic treatment for the entire S. chamaecyparissus complex, although important contributions were published by Marchi and coworkers (Marchi & D'Amato, 1973;Marchi & al., 1979) and Arrigoni (1977Arrigoni ( , 1979Arrigoni ( , 1982Arrigoni ( , 2018 for Italy, by Tison & Foucault (2014) and for France, and by Carbajal & al. (2017 for Spain.…”
Section: ■ Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In the last two decades, López-Udias and co-workers (López-Udias & al., 1997;López-Udias & Fabregat, 2002) and especially Rivero-Guerra (2008a,b, 2011 and Rivero-Guerra & Laurin (2012) have studied the S. rosmarinifolia complex, so that its nomenclature and taxonomy seem to have become more stable than in the past. On the contrary, there is no taxonomic treatment for the entire S. chamaecyparissus complex, although important contributions were published by Marchi and coworkers (Marchi & D'Amato, 1973;Marchi & al., 1979) and Arrigoni (1977Arrigoni ( , 1979Arrigoni ( , 1982Arrigoni ( , 2018 for Italy, by Tison & Foucault (2014) and for France, and by Carbajal & al. (2017 for Spain.…”
Section: ■ Introductionmentioning
confidence: 89%
“…Several taxonomic treatments have been published for Santolina, but they are often at odds with each other (Carbajal & al., 2017). For instance, the two treatments for the European continent published by Guinea (1970Guinea ( , 1976 are very different from each other (López-Udias & Fabregat, 2002).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Santolina is a genus of dwarf aromatic shrubs that includes about 26 species endemic to the western portion of the Mediterranean Basin [17][18][19]. According to Oberprieler [20], the diversification of this genus from its closest relative started around 10 million years ago.…”
Section: Introductionmentioning
confidence: 99%
“…apparently restricted to the Balearic Islands. On the basis of phylogenetic analysis of plastidial DNA sequences,Carbajal & al. (2017) suggested that this taxon is more closely related to S. villosa Mill., S. virens Mill., and S. benthamiana Jord.…”
mentioning
confidence: 99%